2019
DOI: 10.1103/physrevc.100.054322
|View full text |Cite
|
Sign up to set email alerts
|

Neutron quadrupole transition strength in C10 deduced from the C10(α,

Abstract: Elastic and inelastic alpha scatterings on 10 C were measured using a 68-MeV/u radioactive 10 C beam incident on the recently developed MAIKo active target system. The phenomenological effective α-N interaction and the point-nucleon density distribution in the ground state were determined from the elastic scattering data. The cross sections of the inelastic alpha scattering were calculated using this interaction and density distribution and were compared with the experiment to determine the neutron quadrupole … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…In addition, the uncertainty from the efficiency estimations due to the incompleteness of the Monte Carlo simulations was approximately 10%, which is taken from Ref. [52]. As discussed in Sec.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the uncertainty from the efficiency estimations due to the incompleteness of the Monte Carlo simulations was approximately 10%, which is taken from Ref. [52]. As discussed in Sec.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the same observations have been reported in Refs. [47][48][49][50][51]62,63]. The neglect of transferring nucleon from projectile to the target during the breakdown process might be the cause of the discrepancy, as stated in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The available experimental elastic scattering angular distributions for the 10 C + 4 He, 10 C + 27 Al, 10 C + 58 Ni and 10 C + 208 Pb systems at different energies [47][48][49][50][51] are subjected to a detailed analysis using different phenomenological, semimicroscopic, and microscopic potentials in order to observe the weak nature of the 10 C projectile on the elastic scattering data.…”
Section: Theoretical Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the recent systematic analysis of the α inelastic scattering demonstrated that the cross sections for the IS0 transitions tended to be overestimated when the density-dependent interaction was used [26]. A more recent analysis of the α inelastic scattering off 10 C employed the density-independent interaction to deduce the IS2 transition strength from the ground state to the 2 + 1 state [44].…”
Section: Dwba Calculationmentioning
confidence: 99%